Make m the subject of the formula p = (m/(a+m))^(1/3)

Question image

Understand the Problem

The question asks us to rearrange the formula (p = (\frac{m}{a+m})^{\frac{1}{3}}) to make (m) the subject.

Answer

$m = \frac{ap^3}{1-p^3}$
Answer for screen readers

$m = \frac{ap^3}{1-p^3}$

Steps to Solve

  1. Raise both sides to the power of 3

To eliminate the cube root, raise both sides of the equation to the power of 3:

$p^3 = (\frac{m}{a+m})^{\frac{1}{3} \cdot 3}$

$p^3 = \frac{m}{a+m}$

  1. Multiply both sides by (a+m)

Multiply both sides by $(a+m)$ to get rid of the fraction:

$p^3(a+m) = m$

  1. Expand the left side

Expand the left side of the equation:

$p^3a + p^3m = m$

  1. Rearrange the equation

Move terms containing $m$ to one side:

$p^3a = m - p^3m$

  1. Factor out m

Factor out $m$ from the right side:

$p^3a = m(1 - p^3)$

  1. Solve for m

Divide both sides by $(1 - p^3)$ to isolate $m$:

$m = \frac{p^3a}{1 - p^3}$

$m = \frac{ap^3}{1-p^3}$

More Information

The formula $m = \frac{ap^3}{1-p^3}$ expresses $m$ in terms of $a$ and $p$.

Tips

A common mistake is not distributing $p^3$ correctly when multiplying it by $(a+m)$. Also, errors can occur when rearranging the terms to isolate $m$.

AI-generated content may contain errors. Please verify critical information

Thank you for voting!
Use Quizgecko on...
Browser
Browser